2013
DOI: 10.18632/oncotarget.1202
|View full text |Cite
|
Sign up to set email alerts
|

Repression of c-Kit by p53 is mediated by miR-34 and is associated with reduced chemoresistance, migration and stemness

Abstract: Repression of c-Kit by p53 is mediated by miR-This is an open-access article distributed under the terms of the Creative Commons AttributioAugust 6n License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACT:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 83 publications
3
109
0
Order By: Relevance
“…In this study, we unequivocally characterized not only miR-34a but also its target SIRT1 as a determinant player during DCA-induced apoptosis in primary rat hepatocytes. In fact, the functional role and significance of the p53/ miR-34a axis have been expanding in these last years, not only in apoptosis (56) but in cancer as well (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we unequivocally characterized not only miR-34a but also its target SIRT1 as a determinant player during DCA-induced apoptosis in primary rat hepatocytes. In fact, the functional role and significance of the p53/ miR-34a axis have been expanding in these last years, not only in apoptosis (56) but in cancer as well (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time Impedance Measurement-Determinations of cellular impedance as a measure of cell proliferation were performed as described previously (39). Twenty-four hours after seeding, DOX was added to the respective wells.…”
Section: Methodsmentioning
confidence: 99%
“…MiR-34, a tumor suppressor miRNA family, is considered to be a critical mediator of p53 function [12][13][14] . Several studies have demonstrated its role in resistance or sensitization to anticancer drugs [15,16] . We found two new targets of sirolimus, p21-activated protein kinase 1 (PAK1) and the ABCB1/MDR1 genes.…”
Section: Introductionmentioning
confidence: 99%